Written in starlight - Ibañez, Isabel (Novelist) (Page Street Publishing, 2022)
Banished from Inkasisa to the Yanu Jungle, Catalina knows her life is in danger but is absolutely certain her destiny is to rule. Rescued by the son of her former general, she is incorporated into a years-in-progress plan to ally with the fierce Illari people and raise an army to retake her throne--and Catalina's abilities as a seer may be the only thing that will convince them to help. If only she was actually able to predict the future...